Differentiate the integral

Calculus Level 3

f ( x ) = x x 2 x t d t f(x) = \int _{x} ^{x^{2}} \frac{x}{t} \, dt

The real valued function f ( x ) f(x) is defined as the definite integral shown above. What is the value of f ( e 2 ) f'(e^2) ?


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Pranshu Gaba
May 2, 2016

Relevant wiki: Differentiation Under the Integral Sign

We can solve this problem in two ways. We can find the expression for f ( x ) f(x) first, and then differentiate it. Another way is to use the general form of Leibniz integral rule


Method 1 : Finding the expression for f ( x ) f(x)

We can treat x x as a constant, since we are integrating with respect to t t .

f ( x ) = x x 2 x t d t = [ x ln ( t ) ] x x 2 = x ln ( x 2 ) x ln ( x ) = x ln ( x 2 x ) = x ln ( x ) \begin{aligned} f(x) & = \int _{x} ^{x^{2}} \frac{x}{t} \, dt \\ & = \big[ x \ln(t) \big] ^{x^2} _x \\ & = x \ln(x^2) - x \ln (x) \\ & = x \ln \left(\frac{x^2}{x} \right) \\ & = x \ln(x) \end{aligned}

The integral is equal to f ( x ) = x ln ( x ) f(x) = x \ln (x) . Note that this is defined only for positive x x .

We can find its derivative using the product rule . f ( x ) = 1 + ln x f'(x) = 1 + \ln x

When we substitute x = e 2 x = e^2 , we get f ( e 2 ) = 1 + ln ( e 2 ) = 1 + 2 = 3 f'(e^2) = 1 + \ln(e^2) = 1 + 2 = 3 .


Method 2: Using the general form of the Leibniz integral rule

If g ( x , t ) g(x,t) and its partial derivative with respect to x x , g x ( x , t ) g_x(x, t) are continuous in x t x 2 x \leq t \leq x^2 , and if a ( x ) , b ( x ) , a ( x ) , b ( x ) a(x), b(x), a'(x), b'(x) are all continuous if x x belongs to the interval x 0 x x 1 x_0 \leq x \leq x_1 ; then for the interval x 0 x x 1 x_0 \leq x \leq x_1 , the following holds true:

d d x ( a ( x ) b ( x ) g ( x , t ) d t ) = g ( x , b ( x ) ) b ( x ) g ( x , a ( x ) ) a ( x ) + a ( x ) b ( x ) x g ( x , t ) d t \frac{d}{dx} \left( \int_{a(x)} ^{b(x)} g(x, t) \, dt \right) = g(x, b(x)) \cdot b'(x) - g(x, a(x)) \cdot a'(x) + \int _{a(x)} ^{b(x)} \frac{\partial}{\partial x} g(x, t) \, dt

In our problem, a ( x ) = x a(x) = x ; b ( x ) = x 2 b(x) = x^2 , g ( x , t ) = x t g(x, t) = \frac{x}{t} .

f ( x ) = x x 2 ( 2 x ) x x 1 + x x 2 1 t d t f'(x) = \frac{x}{x^2} \cdot (2x) - \frac{x}{x} \cdot 1 + \int _{x} ^{x^2} \frac{1}{t} \, dt

On simplification, we obtain f ( x ) = 1 + ln x f'(x) = 1 + \ln x . Substituting x = e 2 x = e^2 yields f ( e 2 ) = 3 f'(e^2) = 3 _\square

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...